Studies on Voltaire and the eighteenth century 378 (Voltaire Foundation, 2017)
D. Gillian Thompson, A modern persecution: Breton Jesuits under the suppression of 1762-1814 Daniel Cardinal, Between Locke and Leibniz: Condillac and the camera obscura Paul G. Beidler, The aesthetic of scientific discovery: Hume, Sterne, and the literary sketch William Scott, Anxieties and aspirations: problems of educational reform on the eve of the French Revolution Paul van Gestel, Dutch reactions to Thomas Paine’s Age of reason Richard Whatmore, ‘Good books and bad morals’: Jean-Baptiste Say’s assessment of the French Revolution Résumés